More ideational than material: Exploring the contemporary role of student voices in Chilean universities - Darwin, Stephen (Education Policy Analysis Archives, 2022)
A key promise of neoliberalist ideologies in higher education is the valorization of student choice as a means of (re)shaping practices and improving the responsiveness of institutions. The power of this neoliberal imaginary (Ball, 2012) was grounded in market-like policies that demanded institutional accountability to both afford competition and maximizing prospects of student satisfaction. A key consequence of this imperative has been burgeoning institutional and system-level investment in metric-based instruments designed to measure and compare student experiences, engagement or satisfaction. However, how effective of these neoliberal policies been in empowering student choice and in producing more reflexive institutions? The research reported here investigated the influence of student voices in one of the earliest adopters of this neoliberal imaginary: the Chilean higher education system. This qualitative study explored the contemporary institutional role and function of student voices using a university typology, with data developed through artefact analyses and interviews with educational leaders. The findings suggest that institutions have heterogeneous orientations ranging from pseudo-democratic to instrumental forms of engagement, reflecting the distinctive sociocultural histories of institutions. However, the outcomes suggest that student voices are not a substantial presence in quality assurance or improvement practices.